Analisis Komparatif Pembiayaan UMKM di PT BPRS PNM Mentari Garut dengan Kredit UMKM di Bank Perumda BPR Garut KCP Limbangan - Nisa, Khoerun; Nur’aeni, Nur’aeni; Jamaludin, Jujun (Jurnal Dimamu, 2024)
Based on the observation results, the background of this research is that the number of customers for MSME at PT BPRS PNM Mentari Garut financing products is far greater than MSME credit products at  Bank Perumda BPR Garut KCP Limbangan. This study aims to determine the comparison between MSME financing at PT BPRS PNM Mentari Garut with MSME credit at Bank Perumda BPR Garut KCP Limbangan in terms of terms, conditions, procedures and margin/interest calculations seen from the SWOT analysis. The object of this study is MSME financing products at PT BPRS PNM Mentari Garut with MSME loans at Bank Perumda BPR Garut KCP Limbangan, using a comparative qualitative method with the help of SWOT analysis and the type of data is primary data. Using data collection techniques through observation, interviews, documentation studies and literature studies. The results of this study indicate that MSME financing products and MSME loans are seen from the strengths (Strenght), namely, there are 7 conditions for applying for MSME financing and 11 conditions for applying for MSME loans, for weakness, there are 5 provisions for applying for MSME financing and 7 conditions for applying for MSME loans, From the opportunities, there are 5 stages of procedures for applying for MSME financing and 5 stages of procedures for applying for MSME loans, seen from threats, namely, there is competition for marketing credit products with other banks that apply lower interest rates than Perumda BPR Garut KCP Limbangan banks.